Continuous cooling transformation diagrams of HSLA steel for seamless tubes production - Schindler I.; Kawulok R.; Seillier Y.; Kawulok P.; Opěla P.; Rusz S.; Vodárek V.; Turoň R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The CCT and two DCCT diagrams were constructed for the HSLA steel containing Cr, V, Nb, and N microadditions, taking into account industrial processing parameters of this material in a seamless tubes rolling mill. The typical finish hot rolling temperature of 1173 K was used for the construction of the standard CCT diagram and the effect of previous austenite deformation at this temperature was evaluated in the DCCT diagram. Another DCCT diagram was developed after heating at 1553 K, followed by plastic deformation at 1173 K. The prior austenite grain size in the hot rolled material after heating at 1173 K was approx. 10 μm, the heating of the as-cast material at 1553 K resulted in the prior austenite grain size over 200 μm. The effect of the previous austenite deformation after low-temperature heating on the CCT diagram was negligible. The high-temperature heating showed a great influence on the austenite decomposition processes. The Ferrite-start temperature was significantly reduced at high cooling rates and the preferred decomposition of coarse grained austenite to acicular ferrite suppressed the bainite transformation at medium cooling rates. The developed DCCT diagrams can be used for the prediction of austenite decomposition products during the cooling of the seamless tubes from the finish rolling temperature. The CCT diagram can be utilized for the quality heat treatment of tubes.